The Role of Financial Sector in Driving Economic Growth - Chmielewski, Jan; Wawrzak, Sebastian (Journal of Finance and Financial Law, 2025)
The purpose of the article. This study verifies whether multidimensional financial-sector development – measured with the IMF composite indices of depth (FDI), access (FMI) and efficiency (FII) – influences key macroeconomic and social outcomes in ten high-income EU economies between 2010 and 2023. Methodology. Standardized annual data was taken from the World Development Indicators and the IMF Financial Development Index Database. Pearson correlation coefficients were calculated for each country and variable pair. The statistical findings were then interpreted case-by-case to capture both short-term relationships and structural patterns. Results of the research. Greater financial depth proved positively related to price stability and to an expansion of private-sector credit. In the short run, however, it showed no significant effect on GDP growth and coincided with a fall in household saving rates and a temporary rise in unemployment – evidence of the nonlinear, stage-dependent nature of the finance-growth nexus. The findings imply that policy makers in advanced economies should focus on balancing further financial deepening with safeguards that counteract labor-market frictions and excessive consumption growth.